PENGEMBANGAN STRATEGI PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK MELALU PENDEKATAN KESEHATAN MASYARAKAT - Dyah Ambarwati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Recently, Police arrested a French national who had the initials FAC for sexually assaulting 305 street children underage. These cases often occur because children are considered the weakest group. This study is a literature review that will describe programs for preventing sexual violence in children concerning e-journals for the last five years. Based on this program, the authors want to develop efforts to prevent sexual violence using a public health perspective. The results of this study identified that women have a strategic position to be able to make efforts to prevent sexual violence before marriage. Then, the prevention efforts in pre-marriage programs consist of: (1) balanced nutritional intake of women of childbearing age, (2) conduct pre-marital medical check-up, and (3) get married at the recommended age.